CHARACTERISTIC OF POLY LACTID ACID (PLA)/ COIR WITH ADDITION OF CHITOSAN VARIATIONS FOR REVIEWING PLASTIC MATERIALS - Ridwan; Rihayat, Teuku; Saputra Ismy, Adi; Ilmi, Awanis; Aidy, Nurhanifa; Aida, Atiqah (International Journal of Research -GRANTHAALAYAH, 2022)
Poly lactic acid or poly lactide (PLA) is a natural polymer that is biodegradable, thermoplastic and is an aliphatic polyester made from renewable materials such as young kepok banana starch. Poly lactic acid with the chemical formula CH3CH(OH)COOH is a biodegradable polymer obtained from the combination of lactic acid monomers. Therefore, in this study the PLA polymer as a matrix was added with fillers in the form of Coir and Chitosan. Coir is a coconut fiber that has been widely used by researchers for decades. Chitosan has been widely used as an important and promising biopolymer material in tissue engineering because of its anti-microbial activity, biodegradability, biocompatibility, and non-toxicity. The characteristics resulting from the combination of these three materials resulted in 4 samples, namely the fixed variable PLA with variations of Coir and Chitosan. Sample 1 Coir/Chitosan ( 90:10 (%)) produces a tensile strength value of 80 MPa. Sample 2 Coir/Chitosan (80:20 (%)) yielded a tensile strength of 55 MPa. Samples of 3 Coir/Chitosan (70:80 (%)) yielded a tensile strength of 48 MPa. Samples of 4 Coir/Chitosan (60:40 (%)) produced a tensile strength of 30 MPa. The FTIR test on sample 1 resulted in a new compound found in the PLA/Coir/Chitosan composite, namely the compound N=C=O which is an isocyanate group at the peak of the 2279.86 cm-1 group. While the SEM test which shows the physical structure of the sample composition of PLA with the addition of Coir/Chitosan (90:10%) is the sample with the best morphology.